Building resilience to climate shocks in Ethiopia - Koo, Jawoo; Thurlow, James; ElDidi, Hagar; Ringler, Claudia; De Pinto, Alessandro (International Food Policy Research Institute, 2019)
Ethiopia has made consistent progress in improving development indicators, but vulnerability to extreme weather events is a continuing concern, especially for people reliant on agriculture for their livelihoods. The 2015/16 El Niño event caused both a severe drought and flooding, which highlighted the remarkable improvements in the country’s resilience and the remaining challenges in ensuring that everyone “bounces back” relatively quickly from adverse climatic shocks. Given the links between climate change, cyclical droughts, and poverty, and the high cost of emergency humanitarian assistance, the Government of Ethiopia and development partners decided to review the country’s resilience programming and identify opportunities and challenges to building greater resilience into the agricultural system. This work included three components: a review of the literature and government programs on resilience in Ethiopia; key informant interviews in several regions of the country; and quantitative crop modeling and economywide analyses to inform resilience programming.